GROWTH PERFORMANCE AND COCOON PRODUCTION OF SILKWORM (Bombyx mori L) ON DIFFERENT FREQUENCY OF FEEDING AND AGE OF LEAVES - Priyantini Widiyaningrum (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
The aim of this study was to evaluate the effects of different frequency feeding and aging of leaves on increasing weight of silkworm instar IV-V and cocoon production. The research was conducted in Cultivation Center of Silkworm Candiroto, Temanggung. The research design was Factorial Design with three level of age from the leaves (the third – fourth leaves from tip of leaf; fifth-sixth leaves from tip of leaf; sevent-eight leaves from tip of a leaf, and three level of feeding frequency 3, 4, 5 times/day). The parameter observed were average daily gain (ADG), weight of cocoon, and weight of empty cocoon. The data gained were analyzed by analysis of variance and to find out the difference caused on the treatments, Duncan Multiple Range Test was used. It is concluded that the different frequency of feeding and age of leaves is significant (P < 0.05) in ADG of silkworm and weight of empty cocoon. The seventh- eight leaf from tip of a leaf, and frequency of feeding five times/day resulting ADG and empty cocoon of the best.